2020
DOI: 10.1002/ange.201914480
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophane‐Type Chlorin Dimers from Dynamic Covalent Chemistry of 2,18‐Porphyrinyl Dicyanomethyl Diradicals

Abstract: 2,18‐Bis(dicyanomethyl)‐substituted NiII porphyrin 8 and ZnII porphyrin 11 were prepared and subjected to oxidation with PbO2 in CH2Cl2 at 298 K to give cyclophane‐type chlorin dimers (9)2 and (12)2 as a consequence of double recombination of biradicals 9 and 12, respectively. Dimer (9)2 takes a syn‐conformation of two distorted NiII chlorins but (12)2 takes an anti‐conformation of relatively planar ZnII chlorins. At 298 K, dimer (9)2 is stable and its 1H NMR spectrum is sharp but becomes broad at high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Herein we report that the stabilization of a radical as well as its dynamic covalent bonding can be efficiently controlled by the coordination of a Lewis acid. We choose Lewis acid B(C 6 F 5 ) 3 (BCF) and the σ‐dimer of phenylamine substituted dicyanomethyl radical for study on the basis of considering: (a) Equilibria between dicyanomethyl radicals and their σ‐dimers recently have been an excellent model of DCC (Scheme 1b) [5, 8–31] . The stability of dicyanomethyl radicals has been systematically studied by structural modification; (b) BCF is an oxidizing agent and can oxidize an organic molecule to a radical cation by single electron transfer [33, 34] .…”
Section: Methodsmentioning
confidence: 99%
“…Herein we report that the stabilization of a radical as well as its dynamic covalent bonding can be efficiently controlled by the coordination of a Lewis acid. We choose Lewis acid B(C 6 F 5 ) 3 (BCF) and the σ‐dimer of phenylamine substituted dicyanomethyl radical for study on the basis of considering: (a) Equilibria between dicyanomethyl radicals and their σ‐dimers recently have been an excellent model of DCC (Scheme 1b) [5, 8–31] . The stability of dicyanomethyl radicals has been systematically studied by structural modification; (b) BCF is an oxidizing agent and can oxidize an organic molecule to a radical cation by single electron transfer [33, 34] .…”
Section: Methodsmentioning
confidence: 99%
“…92,93 In 2020, Osuka et al prepared 2,18-bis(dicyanomethyl)-substituted Ni II porphyrin radical 26 and Zn II porphyrin radical 27, which can undergo dimerization to afford cyclophane type chlorin dimers 26 2 and 27 2 , respectively. 94 The X-ray crystallographic analysis revealed that dimer 26 2 adapted a synconformation with two distorted Ni II chlorins while 27 2 displayed an anti-conformation with relatively planar Zn II chlorins.…”
Section: Dicyanomethyl Radicalmentioning
confidence: 97%
“…92,93 In 2020, Osuka et al prepared 2,18-bis(dicyanomethyl)-substituted Ni II porphyrin radical 26 and Zn II porphyrin radical 27 , which can undergo dimerization to afford cyclophane type chlorin dimers 26 2 and 27 2 , respectively. 94 The X-ray crystallographic analysis revealed that dimer 26 2 adapted a syn -conformation with two distorted Ni II chlorins while 27 2 displayed an anti -conformation with relatively planar Zn II chlorins. The equilibrium between monomers 26 / 27 and respective dimers 26 2 / 27 2 based on reversible radical–radical dissociation and a recombination process was observed at high temperature for 26/26 2 and at room temperature for 27/27 2 .…”
Section: Carbon-centered Radical-based Dynamic Covalent Chemistrymentioning
confidence: 97%
“…Currently, several dicyanomethylene‐substituted compounds have been identified to undergo reversible σ‐oligomerization through the formation of long (CN) 2 C‐C(CN) 2 σ‐bonds, giving rise to cyclophanes and other macrocyclic compounds [3, 5–7, 11, 15, 24–28] . For instance, our teams have found that carbazole‐based diradicals are able to form stable cyclophane macrocycles upon soft external stimuli, showing a strong chromic effect from violet to white [6] .…”
Section: Introductionmentioning
confidence: 93%